The Relation Between Oxygen Therapy Duration and Free Radical Generation In Infants With bronchiolitis - Hannun, R.M; Al- Goubori, A.G; AL-Equabi, M.A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Oxygen therapy (OT) is considered an essential process for survival for the i nfants with bronchiolitis > However, it may reach the status of being harmful when using it for along beriod . We , here, attempted to shed a light on relations between oxygen therapy duration(OTD) and each of serum malondialdehyde (MDA) that is used as index for free radical generation , and serum albumin level , in infants with bronchiolitis . Our results confirmed that (OTD) from (1-48) hr. was non effective, while from 49 was very effective where a grave in crease in serum (MDA)level and a decrease in serum albumin concentration were observed during that time . The relation between age and serum albumin level proved that (OTD)plays an important role as a pathogenitic factor in infants aged (l-3)months